Macrophage Function in Calcium Oxalate Kidney Stone Formation: A Systematic Review of Literature - Taguchi, Kazumi; Okada, Atsushi; Unno, Rei; Hamamoto, Shuzo; Yasui, Takahiro (Frontiers in Immunology, 2021)
Background The global prevalence and recurrence rate of kidney stones is very high. Recent studies of Randall plaques and urinary components in vivo, and in vitro including gene manipulation, have attempted to reveal the pathogenesis of kidney stones. However, the evidence remains insufficient to facilitate the development of novel curative therapies. The involvement of renal and peripheral macrophages in inflammatory processes offers promise that might lead to the development of therapeutic targets. The present systematic literature review aimed to determine current consensus about the functions of macrophages in renal crystal development and suppression, and to synthesize evidence to provide a basis for future immunotherapy. Methods We systematically reviewed the literature during February 2021 according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Articles investigating the relationship between macrophages and urolithiasis, particularly calcium oxalate (CaOx) stones, were extracted from PubMed, MEDLINE, Embase, and Scopus. Study subjects, languages, and publication dates, were unrestricted. Two authors searched and screened the publications. Results Although several studies have applied mixed modalities, we selected 10, 12, and seven (total, n = 29) of 380 articles that respectively described cultured cells, animal models, and human samples. The investigative trend has shifted to macrophage phenotypes and signaling pathways, including micro (m)-RNAs since de Water et al. (1999) discovered that macrophages are involved in kidney stones. Earlier studies of mice-associated macrophages with the acceleration and suppression of renal crystal formation. Later studies found that pro-inflammatory M1- and anti-inflammatory M2-macrophages are involved. Studies of human-derived and other macrophages in vitro and ex vivo showed that M2-macrophages can phagocytose CaOx crystals, which suppresses stone development. The signaling mechanisms that promote M2-like macrophage polarization toward CaOx nephrocalcinosis, include the NLRP3, PPARγ-miR-23-Irf1/Pknox1, miR-93-TLR4/IRF1, and miR-185-5p/CSF1 pathways. Proteomic findings have indicated that patients who form kidney stones mainly express M1-like macrophage-related proteins, which might be due to CaOx stimulation of the macrophage exosomal pathway. Conclusions This systematic review provides an update regarding the current status of macrophage involvement in CaOx nephrolithiasis. Targeting M2-like macrophage function might offer a therapeutic strategy with which to prevent stones via crystal phagocytosis.